Pembangunan program latihan taktikal dan kesannya dalam kalangan pemain hoki remaja lelaki / Noorzaliza Osman - Noorzaliza, Osman (2017)
Tactical components is one of the important components of sports performance for athletes, apart from the physical, technical and psychological components. This study was conducted to build up andexamine at the effect of tactical training intervention on the level of knowledge, decision making accuracy and performance of the tactical action among boy’s hockey player. The variable measured were tactical level of knowledge, tactical decision making accuracy and performance of the tactical action. A total of 30 male hockey players from Bukit Jalil Sports School were voluntarily involved in this study and the selection of subjects is based on the background of the sports to be studied. They are divided into two groups, namely treatments and the control group through simple random sampling. Treatment group has been undergoing tactical training intervention program for eight weeks (involves theoretical sessions, practical sessions tactical which include accuracy decision making and practical in game situations). Tactical level of knowledge was measured using the Tactical Skills Inventory for Sports (TACSIS), which was translated into Bahasa Malaysia, while the accuracy of decision-making was measured by Tactical Video Clip Questions (SOTAVlK) and tactical action in turn was measured by the performance of the Tactical Action (PATH) Hockey (3 vs 3 mini match situation).Test data was analyzed using SPANOVA. Results of this study found significance difference between pre- and post-test in tactical level of knowledge (Scale A=knowing about ball action [F(1,28)=86.86.05,p<0.05], (Scale B=knowing aboutothers [F(1,28)=22.95,p<0.05], Scale C=positioning and deciding [F(1,28)=18.51,p<0.05], the scale of D=acting in changing situations [F(1,28)=26.66, p<0.05]. The accuracy of decision-making (part A attacker situasition’s video clip [F (1,28)=34.55,p<0.05] and (part B defence situation’s video clip) [F(1,28)=169.23, p<0.05] and tactical action performance (PATHAB succeeded action in attacker situation part A [F(1,28)=25.98,p<.0.05] and (PATHBB succeeded action in defence situation part B [F(1,28)=0.87,p<0.05]. This study also revealed significance difference between treatment and control group knowledge(Scale A=knowing about ball action [F(1,28)=159.10,p<0.05], (Scale B=knowing aboutothers [F(1,28)=3.95,p<0.05], (Scale C= positioning and deciding [F(1,28)=24.73,p<0.05], the scale of D = acting in changing situations [F(1,28)=55.15,p<0.05]. The accuracy of decision-making (part A attacker situasition’s video clip)[F(1,28)=122.59,p<0.05] and (part B defence situation’s video clip) [F(1,28)=169.01,p<0.05] and for tactical action performance (PATHAB succeeded action in attacker situation part F(1,28)=29.12,p<0.05] and (PATHBB succeeded action in defence situation part [F(1,28)=1.27,p<0.05]. From the findings we can conclude that this tactical training intervention is suitable for boy’s hockey player and measurement of instruments may be used to evaluate the tactical knowledge, accuracy in decision making and players action tactical performance before and during training. This study suggest coaches to emphasize on training the tactical components in team or athlete’s annual training program.